Effects of Concentrating Resistance to Northern Leaf Blight of Maize on Agronomic Traits - Ojulong, H.F.; Adipala, E.; Rubaihayo, P.R. (East African Agricultural and Forestry Journal, 1995)
Lack of appropriate maize varieties in Uganda has • been cited as one of the major factors limiting the production of this crop in the country. Thirty-five per cent of the maize grown in the country comprises improved open-pollinated varieties; 60% comprises unimproved open-pollinated varieties which have resulted from planting many generations of the formally improved open-pollinated varieties (Baguma, 1992). This, coupled with the introduction of susceptible cultivars from Centro International de Majeramiento de Maizy Trigo, Mexico (CIMMYT) led to an outbreak of northern leaf blight (NLB) -in 1988